PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN ARUS KAS OPERASI TERHADAP FINANCIAL DISTRESS - Antoni, Febia Garcia; Rahmi, Siti; Rahmawati, Novia; Nurhuda, Nurhuda (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2025)
Financial Distress is a condition where a company experience a decline in financial condition which is the beginning before the bankcruptcy occurs. The problem of financial distress can be seen from the condition of the company’s profits which fallen continiusly or even had negative profits for several years. This research aims to empirically test the effect of profitability, liquidity, leverage, and cash flow operating on financial distress. The population in this research is 108 consumer good non-cyclicals companies sector listed in Indonesian Stock Exchange (IDX) for the 2021-2023 period. The sample in this study was 71 companies using a purposive sampling technique. The technique in this research uses multiple linear analysis test. The result of the research show that profitability, liquidity, and leverage have significant effect on financial distress. Meanwhile, cash flow operating has no effect on financial distress.